Interplay between Natural Killer Cells and Anti-HER2 Antibodies: Perspectives for Breast Cancer Immunotherapy - Muntasell, Aura; Cabo, Mariona; Servitja, Sonia; Tusquets, Ignasi; Martínez-García, María; Rovira, Ana; Rojo, Federico; Albanell, Joan; López-Botet, Miguel (Frontiers in Immunology, 2017)
Overexpression of the human epidermal growth factor receptor 2 (HER2) defines a subgroup of breast tumors with aggressive behaviour. The addition of HER2-targeted antibodies (i.e. trastuzumab, pertuzumab) to chemotherapy significantly improves relapse-free and overall survival in patients with early stage and advanced disease. Nonetheless, considerable proportions of patients develop resistance to treatment, highlighting the need for additional and co-adjuvant therapeutic strategies. HER2-specific antibodies can trigger NK cell-mediated antibody-dependent cellular cytotoxicity and indirectly enhance the development of tumor-specific T cell immunity; both mechanisms contributing to their anti-tumor efficacy in preclinical models. Antibody-dependent NK cell activation results in the release of cytotoxic granules as well as the secretion of pro-inflammatory cytokines (i.e. IFNγ and TNFα) and chemokines. Hence, NK cell tumor suppressive functions include direct cytolytic killing of tumor cells as well as the regulation of subsequent anti-tumor adaptive immunity. Albeit tumors with gene expression signatures associated to the presence of cytotoxic lymphocyte infiltrates benefit from trastuzumab-based treatment, NK cell-related biomarkers of response/resistance to HER2-specific therapeutic antibodies in breast cancer patients remain elusive. Several variables including: i) the configuration of the patient NK cell repertoire; ii) tumor molecular features (i.e. estrogen receptor expression); iii) concomitant therapeutic regimens (i.e. chemotherapeutic agents, tyrosine kinase inhibitors) and iv) evasion mechanisms developed by progressive breast tumors, have been shown to quantitatively and qualitatively influence antibody-triggered NK-cell responses. In this review we discuss possible interventions for restoring/enhancing the therapeutic activity of HER2 therapeutic antibodies by harnessing NK cell anti-tumor potential through combinatorial approaches, including immune checkpoint blocking/stimulatory antibodies, cytokines and TLR agonists.